Quantifying altitudinal diversity of moth assemblages in Gunung Serapi, Sarawak - Hanis, Abdul Razak (Universiti Malaysia Sarawak (UNIMAS), 2004)
This research was done to quantify moth assemblages in tenns of species diversity, along 3 chosen altitudinal sites at Gunung Serapi, Sarawak. The 3 sites were at 200-300m, at 500600m and at 800-900m above the sea level, corresponding to Lower Mixed Dipterocarp Forest, Mid-Mixed Dipterocarp Forest and Upper Mixed Dipterocarp Forest, respectively. Modified Pennsylvanian Light traps were used; 3 nights trapping per site using 2 light traps. Data collected showed a rich diversity of moth assemblages, characterized by high abundance of Arctiidae, Geometridae and Noctuidae. Simpson's and Shannon-Wiener indices were calculated for both actual data and averaged data. Test using Shannon-Wiener value and Zar's (1996) modified t-test, show a significant difference for site 1 vs. site 3, and site 2 vs. site 3, respectively. Apparently the moth diversity is significantly different between the lower mixed dipterocarp forest (200-300m) and the upper mixed dipterocarp forest (800-900m) and for the mid-mixed dipterocarp forest (500-600m) and upper mixed dipterocarp forest (800-900m), respectively.